Sustainable development : issues and case studies - Chattopadhyay, Srikumar; Sharma, H. S. (Hari Shanker), 1945-; National Association of Geographers, India (New Delhi : Published for Commission on Sustainable Development, National Association of Geographers, India by Concept Pub. Co., 1998)
Case study of Kerala, Karnataka, and West Bengal, India.
Includes bibliographical references and index.
Keywords: Sustainable development -- India -- Kerala -- Case studies; Economic development -- Environmental aspects -- India -- Kerala -- Case studies; Sustainable development -- India -- Karnataka -- Case studies; Economic development -- Environmental aspects -- India -- Karnataka -- Case studies; Sustainable development -- India -- West Bengal -- Case studies; Economic development -- Environmental aspects -- India -- West Bengal -- Case studies